# Step-by-step Solution

## Solve the equation $\left(x+1\right)\left(x-2\right)=0$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$x=-1,\:x=2$

## Step-by-step explanation

Problem to solve:

$\left(x+1\right)\left(x-2\right)=0$
1

Break the equation in factors and set each equal to zero, to obtain

$x+1=0,\:x-2=0$
2

Solve the equation ($1$)

$x+1=0$
3

We need to isolate the dependent variable $x$, we can do that by subtracting $1$ from both sides of the equation

$x=-1$
4

Solve the equation ($2$)

$x-2=0$
5

We need to isolate the dependent variable $x$, we can do that by subtracting $-2$ from both sides of the equation

$x=2$
6

The $2$ solutions of the equation are

$x=-1,\:x=2$

$x=-1,\:x=2$

### Problem Analysis

$\left(x+1\right)\left(x-2\right)=0$

Equations

~ 0.03 seconds